PERFORMANCE OF FECL₃ AND CHIA SEED (SALVIA HISPANICA L.) AS A COAGULANT–FLOCCULANT COMBINATION FOR REMAZOL RED DYE REMOVAL - Fadhila Nita Anugraheni; Qonitah Fardiyah; Barlah Rumhayati (Walisongo Journal of Chemistry, 2026)
Textile dye wastewater contains persistent and potentially carcinogenic pollutants that threaten aquatic ecosystems. This study applied a coagulation–flocculation technique to evaluate the treatment efficiency of FeCl₃ as a synthetic coagulant combined with a natural flocculant derived from chia seeds (Salvia hispanica L.) for the removal of Remazol Red dye. Operational parameters, including pH, initial dye concentration, and coagulation stirring speed, were varied to assess treatment effectiveness. The results showed that the addition of chia seed flocculant significantly increased dye removal efficiency, reaching 99.01% under the optimum conditions of pH 5, an initial dye concentration of 50 mg/L, and a stirring speed of 700 rpm. The percentage removal of Remazol Red dye was determined using a UV-Vis spectrophotometer, while a Fourier transform infrared (FTIR) analysis was used to identify the functional groups present in the resulting flocs. The FTIR results confirmed the proposed mechanism, suggesting that FeCl₃ facilitated charge neutralization and subsequently promoted a polymer-bridging mechanism through natural chia seed polymers. This combined system provides a highly efficient and environmentally friendly alternative for textile wastewater treatment, thereby reducing dependence on purely synthetic chemicals.